Health‐related quality of life and treatment modality among esophageal squamous cell carcinoma survivors: A prospective study using time to deterioration model analysis. Issue 1 (30th October 2020) - Liu, Shuang; Lin, Zheng; Lin, Jianbo; Chen, Huilin; Xie, Qianwen; Rao, Wenqing; Chen, Yuanmei; Yu, Kaili; Hu, Zhijian
Abstract: Background and Objectives: This study aimed to analyze the association between health‐related quality of life and treatment modality among esophageal squamous cell carcinoma (ESCC) survivors. Methods: Patients completed the EORTC QLQ‐C30 and EORTC QLQ‐OES18 at baseline and follow‐up. A time to deterioration model analysis was performed to compare longitudinal EORTC QLQ‐C30/QLQ‐OES18 data between surgery alone and surgery with adjuvant chemotherapy. Results: For EORTC QLQ‐C30 scale, compared with surgery alone, significant delays in time to deterioration in role functioning (16.05 months vs. 15.00 months; p = .045), cognitive functioning (20.80 months vs. 16.26 months; p = .017), social functioning (19.09 months vs. 12.35 months; p = .001), and dyspnea (18.53 months vs. 14.62 months; p = .011) were observed for surgery with adjuvant chemotherapy. For QLQ‐OES18 scale, compared with surgery alone, significant delays in time to deterioration in dysphagia (13.75 months vs. 8.16 months; p = .005), choking when swallowing (20.67 months vs. 15.08 months; p = .001), and dry mouth (21.78 months vs. 17.28 months; p = .039) were observed for surgery with adjuvant chemotherapy. Conclusions: Patients who received postoperative chemotherapy had significant delay in time to deterioration in multiple ESCC‐related symptoms, functions of EORTC QLQ‐C30 and EORTC QLQ‐OES18.